LAMELLICORN BEETLES (COLEOPTERA, SCARABAEOIDEA) OF THE COASTS AND ISLANDS OF THE CASPIAN SEA: A SURVEY OF THE FAUNA - I. V. Shokhin (Ûg Rossii: Èkologiâ, Razvitie, 2015)
Aim. The aim of the study was to determine the characteristics of distribution scarabaeini coasts and Islands of the Caspian Sea. Methods. Used standard methods of data collection and analysis of the material. The material for this work were collected by the authors in numerous expeditions, among which should be noted particularly complex expedition of the Institute of applied ecology on the island Nordby, Chechen, seal, Cully. Also take into account the material given in the literature as faunal summaries (Kryzhanovsky, Medvedev, 1960, Baraud, 1968, Grigoryants, 1983, Nikolaev, 1987, Shokhin, 2002, 2007, Shokhin, Abdurakhmanov, Olejnik, 2012, and others), surveys of the fauna of the former USSR (Medvedev, 1949-1964, Kabakov, 2006), Europe (Baraud, 1992, 1993), and numerous taxonomic revisions. Location. Coasts and Islands of the Caspian Sea. Results. A list of 407 taxa recorded coasts of the Caspian Sea. Main conclusions. The basis of the fauna are species Turanian origin, are also a significant number of species of Mediterranean origin. The fauna of the mainland is divided into three main clusters, generally corresponding to the Northern, Eastern and South-Zapadna coasts. The fauna of the Islands is obediently collectively with unique features.